Self-Assessment of the Professional Competence of Preschool Teaching Student - Kaļķe, Baiba; Baranova, Sanita; Āboltiņa, Līga (Acta Paedagogica Vilnensia, 2022)
One of the objectives of the European Higher Education Area is to promote the development of competences, with an emphasis on those competences that people need to maintain their current quality of life and high level of employability in the face of a changing society and labor market. This study analyzed the self-assessment of student preschool teachers’ professional competence, using a tool (survey) for assessing teachers’ professional competence. A structure of preschool teachers’ professional competence was analyzed. The results indicate that the developed survey can be used as a tool for the self-assessment of teachers’ professional competence. The most highly evaluated sub-competences were general tasks of ensuring professional activity; implementation of learning process; and improvement of professional competence. The data analysis revealed that the question “Is the work related to the field of study?” with the statements included in the survey sections “Implementation of the learning process” and “Improvement of professional competence” is an important indicator in the self-assessment of professional competence among student preschool teachers for the material situation.
Keywords: preschool teachers’ professional competence; teachers’ professional competence; competence assessment; competence self-assessment